Інтродукція актинідії в Лісостепу України. Повідомлення 1. Феноритміка та особливості сезонного розвитку актинідії - Skripchenko, N.V.; Moroz, Р.А. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2004)
The article is devoted to investigation of phenological peculiarities of 5 species of Actinidia Lindl. genus under introduction in Forest-Steppe of Ukraine: A. kolomikta, A. arguta, A. purpurea, A. polygama and A. chinensis. The rhythms of growth, organogenesis of shoots, blossom and fruitage of these species in the region of introduction are investigated. Forest-Steppe climatic conditions of Ukraine suitable for passing of complete cycle of growth and development for introduced species, except A. chinensis.